The Value of Diffusion Weighted MRI in the Detection and Localization of Prostate Cancer among a Sample of Iraqi Patients - Wahid, Hiba M.Abdul; Al-Mosawe, Ammar M.; Kareem, Tara F.; Awn, Anas K.; Nayyef, Qusay T. (AL-Kindy College Medical Journal, 2020)
Background: Prostatic adenocarcinoma is the most widely recognized malignancy in men and the second cause of cancer-related mortality encountered in male patients after lung cancer.Aim of the study:  To assess the diagnostic value of diffusion weighted imaging (DWI) and its quantitative measurement, apparent diffusion coefficient (ADC), in the identification and localization of prostatic cancer compared with T2 weighted image sequence (T2WI).Type of the study: a prospective analytic studyPatients and methods: forty-one male patients with suspected prostatic cancer were examined by pelvic MRI at the MRI department of the Oncology Teaching Hospital/Medical City in Baghdad from September 2017 to September 2018. Thin sections axial T2 and DWI sequences were performed for each patient. Two patients were excluded from the study due to poor image quality (motion artefact). Regions with hypointense signal on T2WI and/or restricted lesion in DWI were determined. The ADC values were measured and the results were registered and sent for biopsy correlation. The sensitivity, specifity, accuracy and other parameters were calculated for T2WI and DWI.Results: The sensitivity and specifity of T2WI in the detection of prostate cancer was about 76.6% and 77% respectively. These improved to 96% and 88.8% by performing the DWI and measuring the ADC value. The mean ADC value was greatly lower in prostatic cancer (about 650x 10-6 mm2 /s) than in normal prostate parenchyma (about 1250 x10-6 mm2 /s) with significant difference between them (p value about 0.04)Conclusion: In practice, using diffusion weighted MRI sequence and its ADC quantitative measurement greatly increases tumor detection in patients suspicious to have prostatic cancer and should be routinely used when doing pelvic MRI for patients with high clinical suspicion.